Speak with confidence a practical guide - Vasile, Albert J. (Longman, 2000)
Practical and written in a conversational style, Speak with Confidence, 8e, is filled with engaging anecdotes and applications that enhance students' learning experience while building their confidence in developing public speaking skills. In response to the ever-shrinking nature of our global community, this edition features expanded coverage of intercultural/multicultural communication and increased coverage of technology in communication.